Normative Values for Cervical and Lumbar Range of Motion in Healthy Young Adults - APTİ, ADNAN; Çolak, Tuğba Kuru; Akçay, Burçin (Galenos Publishing House, 2023)
Objective: The cervical and lumbar spines are the more mobile parts of the spinal column than the thoracic spine. Reference range of motion (ROM) measurements is one of the important clinical outcome measures used in patient assessment and follow-up of treatment efficacy. The aim of this study was to obtain normative values of cervical and lumbar ROM in young adults. Materials and Methods: The sample comprised 300 healthy volunteers (198 female, 102 male, mean age: 21.4±1.9 years, range, 18-29 years). Cervical (C) and lumbar (L) ROM values were measured in three planes with a two-arm digital goniometer according to the American Academy of Orthopaedic Surgeons (AAOS) criteria. The mean ROM measurements were analyzed according to gender using the Mann-Whitney U test. Results: Cervical ROM values were determined to be: cervical flexion 57.7±8.2º, extension 59.1±10.2º, right-left lateral flexion 42.1±7.9º-41.4±7.7º, and right-left rotation 71.1±10.5º-70.2±9.7º. There was no statistically significant difference between the genders with respect to the cervical ROM (p>0.05). The lumbar ROM values were determined to be lumbar flexion 69.9±14.5º, extension 40±10.2º, right-left lateral flexion 36.3±6.4º-36.2±6.6º, and right-left rotation 38.4±8.7º-38.6±9.4º. The lumbar flexion ROM values were statistically significantly higher in females than in males (p=0.043). Conclusion: The flexion and extension angles of the lumbar spine in the sagittal plane were higher in females than in males, and there was no difference between the genders regarding all the other cervical and lumbar joint ROM values. These goniometrically measured cervical and lumbar ROM values were found to be generally similar to the widely used reference values of AAOS and Kendall McCreary. Further research is needed on the effects of individual differences such as physical activity or inactivity.
Keywords: Cervical; Goniometer; Lumbar; Range of Motion; Spine